Utopia or Oblivion the prospects for humanity - R. Buckminster Fuller (New York, Bantam Books, 1969)
This book explains that efforts to reverse Africa's continuing underdevelopment have failed to date because they have not been consciously aimed at enabling Africa to turn its vast natural resources into wealth; here, Malunga proposes a five step strategy enabling the continent revolutionize and improve the system.
Includes Bibliography
Keywords: Civilization, Modern--1950-